Unexpected roles for DEAD-box protein 3 in viral RNA sensing pathways - BOWIE, ANDREW (My University, 2010)
Detection of viral nucleic acid within infected cells is essential to an effective antiviral response. The retinoic acid-inducible gene-I (RIG-I)-like receptors (RLR) form part of the virus detection repertoire and are critically important in sensing viral RNA in the cytoplasm. Efforts continue to define the signalling components downstream of RLR that are required to induce type I IFN (IFN-? and IFN-?) after viral infection. One surprising finding was that the DEAD (Asp-Glu-Ala- Asp) box helicase DDX3 (DEAD/H Box 3), known for some time to have a number of roles in cellular RNA regulation in the nucleus, has a role in the RLR cytoplasmic signalling pathway involved in IFN-? induction. In this issue of the European Journal of Immunology, an article reports an additional distinct positive role for DDX3 in the RLR RNA sensing pathway. This further emphasises the importance of DDX3 in anti-viral immunity, and is consistent with the idea that viruses target DDX3 for immune evasion.
PUBLISHED
Keywords: DEAD-box protein 3; Immunology, Inflammation & Infection; Nanoscience & Materials